2022
DOI: 10.1021/acsanm.2c01536
|View full text |Cite
|
Sign up to set email alerts
|

Heat Generation in Magnetic Hyperthermia by Manganese Ferrite-Based Nanoparticles Arises from Néel Collective Magnetic Relaxation

Abstract: Collective magnetic relaxation of coupled nanoparticle’s magnetic moments and its influence in magnetic nanoparticle hyperthermia (MNH) therapy are studied by combining experimental data, numerical simulations, and theoretical approaches. Frequency-dependent MNH of Mn-ferrite nanoparticles with different particle sizes and different nanoparticle arrangements, controlled by medium pH and surface coating, revealed that the hyperthermia efficiency could increase or decrease depending on the nanoparticle’s organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 64 publications
3
18
0
Order By: Relevance
“…Another approach to further optimize the heating efficiency may be achieved by tuning the MNP–medium parameters such as dosage (namely MNP concentration) and the viscosity of the medium based on a water/agarose solution. In clinical practice, the iron concentration typically varies between 0.5 and 8.0 mg mL –1 in in vitro studies. , At higher concentration, the shorter the interparticle distance between MNPs, the greater their dipolar interaction with a direct impact on eventual heat release. , Further, recent studies have shown that the heating efficiency changes as a function of the viscosity of the medium. However, there have been only a few studies addressing the different heating mechanisms as a function of medium viscosity. , Finally, for a given set of particle size, magnetic anisotropy, dipolar interactions, and the medium, the external field amplitude and frequency should match the MNP features for the largest heat release in MPH. Using an optimized set of parameters, heat release can be tuned by adjusting the field amplitude or frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach to further optimize the heating efficiency may be achieved by tuning the MNP–medium parameters such as dosage (namely MNP concentration) and the viscosity of the medium based on a water/agarose solution. In clinical practice, the iron concentration typically varies between 0.5 and 8.0 mg mL –1 in in vitro studies. , At higher concentration, the shorter the interparticle distance between MNPs, the greater their dipolar interaction with a direct impact on eventual heat release. , Further, recent studies have shown that the heating efficiency changes as a function of the viscosity of the medium. However, there have been only a few studies addressing the different heating mechanisms as a function of medium viscosity. , Finally, for a given set of particle size, magnetic anisotropy, dipolar interactions, and the medium, the external field amplitude and frequency should match the MNP features for the largest heat release in MPH. Using an optimized set of parameters, heat release can be tuned by adjusting the field amplitude or frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Note that there is no contribution from the GNRs since the eddy’s current loss at this size is negligible. Further studies may help to evaluate if the GNRs are influencing the Néel collective relaxation of the aggregates of MnFe 2 O 4 NPs coupled to the GNRs [ 27 ]. Nevertheless, these hybrid NPs may be used similarly to Ci-MnFe 2 O 4 as a feasible heat generator for MH.…”
Section: Resultsmentioning
confidence: 99%
“…Ci-MnFe 2 O 4 NPs were synthesized via the coprecipitation route by Zufelato et al [ 27 ]. The core, crystal, hydrodynamic sizes, and polydispersity index (PDI) of these MNPs were 16.7, 14, 38 nm, and 0.32, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations